2015
DOI: 10.32734/jpt.v2i1.2878
|View full text |Cite
|
Sign up to set email alerts
|

Remediasi Tanah Tercemar Logam Berat Dengan Menggunakan Biochar

Abstract: ABSTRAKPembangunan industri dan urbanisasi selain dapat meningkatkan kesejahteraan manusia, tetapi juga memberikan efek negatif kepada lingkungan yaitu menghasilkan limbah dalam jumlah yang sangat besar, dan hal ini akan menjadi masalah yang serius bila tidak tangani dengan segera. Penangangan limbah pun masih belum di lakukan dengan serius dan bertanggung jawab sehingga sering dilaporkan adanya lahan yang tercemar akan limbah khususnya limbah logam berat. Logam-logam berat merupakan unsur yang tidak biodegrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 7 publications
0
3
0
11
Order By: Relevance
“…According to the WHO limit the intake of foods that contain heavy metals, Pb is 0.2-0.3 mg•day -1 per person. Agricultural fertilizers, especially phosphate fertilizers containing heavy metals Pb between 5 to 156 g•kg -1 and 7 g•kg -1 of Cd for neutral land [HIDAYAT 2015]. If fertilizer is used continuously with a high dose and intensity may increase Pb and Cd provided in a land so that when the water runoff passing through the agricultural area can increase the concentration of Pb and Cd in the waters.…”
Section: Resultsmentioning
confidence: 99%
“…According to the WHO limit the intake of foods that contain heavy metals, Pb is 0.2-0.3 mg•day -1 per person. Agricultural fertilizers, especially phosphate fertilizers containing heavy metals Pb between 5 to 156 g•kg -1 and 7 g•kg -1 of Cd for neutral land [HIDAYAT 2015]. If fertilizer is used continuously with a high dose and intensity may increase Pb and Cd provided in a land so that when the water runoff passing through the agricultural area can increase the concentration of Pb and Cd in the waters.…”
Section: Resultsmentioning
confidence: 99%
“…Polusi tanah merupakan salah satu masalah pencemaran lingkungan yang menjadi perhatian untuk segera dilakukan tindakan. Meningkatnya pabrik-pabrik yang bertujuan untuk memenuhi kebutuhan penduduk semakin hari semakin bertambah, dan tanpa disadari pabrik tersebut menghasilkan limbah yang cukup, dan bila tidak dikelola dengan baik akan memberikan dampak negatif terhadap lingkungan (Zhang et al 2013;Hidayat 2015).…”
Section: Polutan Dan Polusiunclassified
“…The C/N ratio of organic matter is the comparison between the number of carbon (C) content and the number of nitrogen (N) content present in an organic matter. Based on the results, it is suggested that soil remediation uses phytoremediation method by combining several additives such as biochar and compost to improve nutrient quality and reduce mercury content in soil (Hidayat, 2015;Hamzah, 2012;Lestari, 2020).…”
Section: |mentioning
confidence: 99%